The role of age in labor productivity: how age matters in professional football - Tovar, J. (Journal of Sports Economics, 2026)
This study analyzes age-productivity relationships in professional football using two comprehensive datasets. The first examines detailed OPTA performance data from the Spanish LaLiga, the English Premier League, and the Colombian Liga Águila, creating productivity indices using principal component analysis. The second uses complete career histories from transfermarkt.com for players across Argentina, Brazil, Chile, and Colombia, applying Fantasy Premier League scoring systems. Both datasets consistently demonstrate an inverted U-shaped age-productivity curve. Peak performance occurs at 27.8 years in the EPL and 30.1-30.5 years in LaLiga and Colombian leagues, according to OPTA data. The transfermarkt analysis confirms this pattern, showing peak performance at 29.9 years across South American leagues. The findings reveal a systematic shift toward older peak performance ages in modern football, attributed to advances in sports science, nutrition, and training methods. These results offer valuable insights for talent management, contract negotiations, and career planning in professional sports.